Rol de enfermería en la prevención de infecciones respiratorias agudas en niños de 3 a 5 años del Centro de Salud # 5 Duran Guayas octubre 2018 – abril 2019 - Chávez Aguirre, Priscila Elizabeth (2019)
Having as problematic respiratory infections, which constitute a complex group of diseases caused by various causative agents that affect any part of the respiratory tract, for this reason the present research work focuses on determining the role of nursing in the prevention of infections respiratory symptoms in children from 3 to 5 years of health center # 5 last guayas October 2018 - April 2019. . In the development of this research work qualitative-quantitative modality is applied. Framing the types of research: explorative, descriptive and transversal. The data collection technique to be used is the interview and the survey, by applying questionnaires of questions to the relatives of children aged 3 to 5 years with respiratory infections and nursing professionals from the outpatient area of the health center # 5 Duran Guayas. After analyzing the information collected from the nursing staff, we can establish that the main acute respiratory pathology that occurs in this group of children aged 3 to 5 years in the health center # 5 Duran Guayas is pharyngotonsillitis; for which parents mostly said that they knew the symptoms that occur during a respiratory condition, but most do not realize the importance of not self-medicating and go to the home first. Concluding that the role of nursing for the prevention of this type of infections is of great importance, since through an educational role we can reach users and communities for the prevention and attention to this type of pathologies